Challenges and prospects in group-based assignments at higher learning institutions in Malaysia - Mhd. Sarif, Suhaimi (2010)
The pros and cons of group-based assignments received well attention by education and training researchers. The study obtained the opinions of Business Administration students about the problems that they possibly identified in group-based assignments and to propose solutions on how to improve groupbased assignments through an instrument (questionnaire). The instrument is designed to be one sheet of A4 so that it appears to be convenient and will not consume much of the respondents’ time. It was distributed to students during class time and collected after 30 minutes. The total number of student respondents who participated in this study is 150, which comprised 40 (36%) male and 110 (64%) female. Respondents identified very serious problem related to group-based assignment which is free riding, which means some members of the group do not share fair share of work in completing the group-based assignments. Thus, the majority of respondents is not in favor of group-based assignments due to this serious problem and suggested the lecturers to discontinue using group-based assignments. However, some of the respondents insisted that group-based assignments can be implemented provided that the instructors use multiple evaluation methods so that the problems can be addressed. The immediate implication for the practice is that university instructors need to review its group-based assignments to reduce the “free-riding” problems. The study would like to propose the use of multiple evaluation methods on group-based assignments to reduce the free riding problem if university instructors insist to apply group-based assignments. The future research for this study should extend the questionnaire to Business Administration students from other universities to ensure the robustness of the results.